FEEDING MANAGEMENT STATUS OF MANIPURI PONY (Indian Journal of Animal Production and Management, 2013)
The objective of the present study is to generate research based information on the various feeding practices followed by Manipuri Pony owners, by conducting systematic survey in the breeding tract. During the survey, 215 pony owners and farmers in 3 districts were interviewed using well prepared questionnaire. The study revealed that about 36.28% of the animals got their feeds under open grazing practices almost throughout the year while another 36.28% of the pony owners were found to practice tethering-cum-open grazing system. 27.44% of the owners maintained their animals, only on tethering during daytime. It was known that 44.60% of the Pony owner supplemented procured green grass to the tethered animals 1-2 times daily. The farmers usually supplied 2 bundles (15kg) of rice straw 1-2 times daily per adult animal, after being cut and soaked in water and 95.57% gave rice bran in soaked form only during scarcity period, generally by mixing with rice straw. It was also reported that the Pony owners didn’t provide oilcakes and as such protein source is almost completely lacking in the ration. The study revealed that Manipuri Pony were kept by and large on zero input feeding system, depending almost solely on indigenous green grasses grown in the breeding tract and on rice straw produced from the cultivation of paddy.
Keywords: Manipuri Pony; Open grazing; tethering-cum-open grazing; tethering